Effect of long term defoliation by cattle grazing with and without trampling on soil compaction and plant species composition in temperate grassland - Ludviková V.; Pavlù V.; Gaisler J.; Pavlu L.; Hejcman M. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
Here we report the results for soil compaction and plant species changes in mesotrophic temperate Central European grassland after 12-years of grazing management with and without cattle trampling. Five grazing treatments (including intensive and extensive grazing, cutting and grazing with no trampling under permanent fencing), with two replicate blocks, have been applied since 1998. In 2010 species richness, the cover of vascular plant species and bryophytes, sward height and soil penetration resistance were recorded. Long term grazing by large herbivores had a significant effect on soil compaction with the lowest values in the “not trampled” treatment. Legumes and short forbs were supported by intensively defoliated and trampled treatments, whereas tall forbs prevailed under the extensive ones. The cover of tall and short graminoids was not dependent on applied treatments. The “not trampled” treatment had the highest prevalence of bryophytes (with more than 95% domination of Rhytidiadelphus squarosus) and was also the richest in a number of vascular plant species, on the other hand had the least Hill’s evenness index. Long-term defoliation by grazing animals without trampling does not lead to the creation of a typical pasture community. Species forming pasture communities are essentially dependent on both types of disturbances: (i) regular defoliation by grazing and (ii) regular trampling by hooves, which causes a high degree of soil compaction as well as sward disruption.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)